How accurate is the offline analysis of 3D volume datasets in the diagnosis of fetal brain abnormalities?. (16th November 2010) - Salman, MSMA; Mousa, H; Twining, P; Bugg, GJ
Abstract : Aim: To assess accuracy and interobserver reproducibility of the offline analysis of the 3D volume datasets in the diagnosis of fetal brain abnormalities. Methods: Seventy-nine 3D volume datasets were acquired at the time of scanning for women attending a tertiary centre. They included 52 cases with brain abnormalities and 27 normal cases without any brain abnormalities. Postnatal MRI or postmortem examination confirmed the final diagnosis in all cases with brain anomalies. Offline analysis of the 79 unidentified 3D volume datasets was carried out by three fetal medicine experts (E1, E2 and E2) using 4D view software. Experts were blinded to any prior diagnosis or history. Data were collected on special designed data sheet and entered in a specialised database for analysis. Results were compared between examiners and with final definitive diagnosis. Results: 87 anomalies in 52 fetuses were described in the definitive diagnosis. In 88.4% (46/52), 98.1% (51/52) and 92.3% (48/52) of cases these anomalies were correctly diagnosed by E1, E2 and E3 respectively. Cases without brain anomalies were diagnosed by the three experts with agreement of 100%. There was good agreement between 2D and each of the 3D experts; in 86.1% of cases with E1 (k=0.7), 89.9% with E2 (k=0.79) and 88.6% of cases with E3 (k=0.76). Conclusion: Offline analysis of 3D datasets is operator dependant. However, it is a reliable method that can be used to help in the assessment of brain anomalies and it could be a useful adjunct to real time 2D ultrasound.